2014
DOI: 10.1002/lary.25050
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal anatomical study of the cavernous sinus segment of the ophthalmic nerve

Abstract: NA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…One of the variations found in this study has been previously reported: during its entire course on the lateral cavernous sinus wall, CNIV is found in intimate relation with CNVI, as though both structures were fused. This feature was found in 2 specimens (Table ; specimen 8, right side and specimen 4, left side), representing 10% of the total sample, similar to what was previously reported by Dolci et al Variation in the course of the trochlear nerve impacts the surface area of Parkinson's triangle, increasing its area when the nerve is located closer to the oculomotor nerve and decreasing it when closer to the ophthalmic nerve. Rhoton and others has also reported on variations of Parkinson's triangle (Table ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…One of the variations found in this study has been previously reported: during its entire course on the lateral cavernous sinus wall, CNIV is found in intimate relation with CNVI, as though both structures were fused. This feature was found in 2 specimens (Table ; specimen 8, right side and specimen 4, left side), representing 10% of the total sample, similar to what was previously reported by Dolci et al Variation in the course of the trochlear nerve impacts the surface area of Parkinson's triangle, increasing its area when the nerve is located closer to the oculomotor nerve and decreasing it when closer to the ophthalmic nerve. Rhoton and others has also reported on variations of Parkinson's triangle (Table ).…”
Section: Discussionsupporting
confidence: 84%
“…To visualize the ophthalmic nerve, a slight mobilization of CNVI is necessary. Reaching this triangle endonasally requires drilling of the lateral wall of the sphenoid sinus and opening the first layer of dura, accessible ventrally (periosteal layer) . In this study, the anteromedial triangle presented an average surface area of 36.07 mm 2 (±4.15 mm 2 ), a similar finding to the results presented by Isolan et al of 36.26 mm 2 (±3.75 mm 2 ) but slightly different than those by Watanabe et al of 41.2 mm 2 (±15.4 mm 2 ).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Several anatomic studies have advocated the feasibility of the anteromedial triangle as the main endonasal entry for the MCF. 23 In the present study, the transposition of V2, expansion of the anteromedial triangle, and separation of the outer meningeal dural layer of the cavernous sinus from the temporal lobe dura led to a substantial increase in the surgical field. Additionally, the floor of the MCF was exposed.…”
Section: Discussionmentioning
confidence: 48%
“…The V1, which represents the upper limb of the anteromedial triangle, was estimated to be approximately 15 mm long from the gasserian ganglion to the SOF. 23 In contrast, the V2 is approximately 4 cm long from the gasserian ganglion to the PPF and can be extended in the IOF up to the ION. 12 However, V1, as part of the sensory triangle, protects the abducent and trochlear nerves running above and medial during the separation of the outer layers of the dura.…”
Section: Discussionmentioning
confidence: 95%